Muhammadiyah and Nahdlatul Ulama Contribution to The Islamic Economics Development in Indonesia - Moh. Mas'udi (Fakultas Agama Islam Universitas Muhammadiyah Yogyakarta, 2023)
Muhammadiyah and Nahdlatul Ulama are the two pillars of the Islamic movement in Indonesia. Muhammadiyah represents the modernist Islamic movement. Meanwhile, Nahdlatul Ulama represents the traditionalist Islamic movement. The role of both in da'wah activities of Islam in religious, educational, and social fields is crucial. In the context of Islamic economics, both contribute to the development of Islamic economics in Indonesia. Through a historical analysis, this study showed that Muhammadiyah and Nahdlatul Ulama have contributed to the Sharia economic development since before the independence of Indonesia in the context of Islamic economic thoughts and practices. With the spirit of the Qur’an, chapter al-Maʿun, the founder of Muhammadiyah, KH Ahmad Dahlan, has inspired Muhammadiyah members to implement Islamic economy in the forms of Islamic philanthropy, which remains preserved until today. At the same time, KH Hasyim Asy'ari, as the founder of Nahdlatul Ulama, initiated Nahdlatut Tujjar as an embryo for the birth of Nahdlatul Ulama.